Examining the Roles of Cognitive and Metacognitive Activities in Translation Performance: Think Aloud Protocol (TAP) Analysis - Saputri, Kurnia; Sari, Farnia; Amaliah, Amaliah (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The purpose of this study is to investigate the cognitive and metacognitive strategies implemented by an English teacher at a Senior High School in Jakarta to understand the cognitive and metacognitive processes used in translating English text into Indonesian text, and vice versa, within a time frame of about 25-30 minutes. This qualitative study aims to explore how cognitive and metacognitive activities may impact students' translation process and help them develop sub-competencies by guiding them through the translation process and identifying strategies used to complete the task. The translation tasks involve translating English text into Indonesian text and vice versa. The tasks provide source text (ST) and Google translation (GT) output as references to assist in translating the texts that are put in post-editing. Each ST consists of 10 sentences that are translated using cognitive and metacognitive activities. The analysis used was the Think Aloud Protocol (TAP) based on Waden’s theory (1991). TAP was used to analyses the taxonomy of cognitive and metacognitive strategies. As the results of the study revealed, the frequency of cognitive strategies used in the Source Text (ST) is higher, indicating a higher complexity that requires additional cognitive effort. On the other hand, the use of cognitive activities decreased, affecting cognitive knowledge and reading strategies that influence cognitive activities. Additionally, metacognitive strategies were found to be more frequently associated with translational problems.